PEMBELAJARAN SASTRA DI SEKOLAH: SEBELUM, SELAMA, DAN SESUDAH PANDEMI (Literature Learning In School: Before, During, And After Pandemic) - Dipa Nugraha (Universitas Islam Negeri Ar-Raniry, 2021)
This article aims to review some discussions on literature learning in Indonesian schools before the pandemic, highlight the real problems, and propose a new model of learning during and after the pandemic. This is a qualitative narrative article. This article interconnects between the references and the writer's personal experience in tackling the problems and proposing solutions. Based on the findings, literature learning in Indonesian schools needs to be made more challenging and fun for students by refreshing the benefit of literature learning within Indonesian literature teachers' minds which is expected to change the teachers' perspective on literature learning into something positive and beneficial in literature learning as well as the use of the internet and digital information technology which serves as students' new learning environment in developing Higher-Order Thinking Skills and 4C skills (critical thinking & problem solving, communication, collaboration, dan creativity & innovation). Meanwhile, the introduction of basic knowledge on the sociology of literature, reader-response criticism, and intertextuality to students will give them a certain framework and direction needed in a critical and challenging reading of literary work. This can be applied in literature learning during and after the pandemic.